Biochemical, structural and clinical analysis of statins’ pleiotropic effects - A. N. Britov; O. A. Gomazkov (Кардиоваскулярная терапия и профилактика, 2009)
Based on the analysis of clinical and experimental studies, an attempt to explain pleiotropic effects of statins and their numerous action mechanisms has been performed. The pleiotropic effect concept includes: (a) medication effects on numerous targets, triggering various biochemical processes in the organism; b) the divergence of biochemical and pathophysiological processes triggered by one target. The pathochemical mechanisms of statins’ effects as HMG-CoA reductase inhibitors are explained. The authors also justify the independence of therapeutic and adverse effects of statins from their lipid and cholesterol-related mechanisms of action.